2010
DOI: 10.1098/rstb.2010.0037
|View full text |Cite
|
Sign up to set email alerts
|

Predicting species distribution and abundance responses to climate change: why it is essential to include biotic interactions across trophic levels

Abstract: Current predictions on species responses to climate change strongly rely on projecting altered environmental conditions on species distributions. However, it is increasingly acknowledged that climate change also influences species interactions. We review and synthesize literature information on biotic interactions and use it to argue that the abundance of species and the direction of selection during climate change vary depending on how their trophic interactions become disrupted. Plant abundance can be contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
499
2
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 663 publications
(511 citation statements)
references
References 93 publications
(114 reference statements)
4
499
2
6
Order By: Relevance
“…Future studies should favour community and ecosystem approaches, including both physical and biotic interactions across trophic levels [59,60], as very little is known about large-scale oceanographic mechanisms driving long-term changes in primary [61] and secondary productivity in sub-Antarctic regions.…”
Section: Resultsmentioning
confidence: 99%
“…Future studies should favour community and ecosystem approaches, including both physical and biotic interactions across trophic levels [59,60], as very little is known about large-scale oceanographic mechanisms driving long-term changes in primary [61] and secondary productivity in sub-Antarctic regions.…”
Section: Resultsmentioning
confidence: 99%
“…Biotic interactions are also expected to be altered by climate change, but their potentially important influence on geographical range limits has not received sufficient attention in empirical studies [10][11][12][13]. The presence of mutualists, competitors, parasites or predators can influence the occurrence and abundance of a species in a given locale, and the strength of these interactions can also change across environmental gradients (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, some researchers have suggested that these biotic interactions may be critical to improve the predictive power of SDMs (Miska and Araújo, 2007;Preston et al, 2008;Boulangeat et al, 2012), especially those across trophic levels (Vander Putten et al, 2010;Barbet-Massin and Jiguet, 2011). It is known that climate change may alter biotic interactions, influencing species distributions both directly and indirectly.…”
Section: Introductionmentioning
confidence: 99%